Feminist standpoint in game-based community landscape planning toolkit development a case study for Artex Compound in Malabon City, Philippines - Bautista, Sheena Hillary M.; Nappy L. Navarra (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Women’s perspectives and narratives in community development are critical in assessing the needs of a community, offering a better understanding of the lived experiences of marginalized groups. To improve the decision-making process and integrate women's lived experiences in community planning and development, the use of feminist standpoint theory and game theory in developing a community landscape planning toolkit is imperative. The study utilizes key informant interviews to gather data on the lived experiences of women, which is later integrated into the development of a community landscape planning toolkit. Using game theory, the toolkit allows players/stakeholders to go through multiple games for discussions on community needs until they can establish their community vision board. This can be achieved by laying out cards that consist of the same themes and strategies collectively decided by players after the provision of information sets. The game output serves as the basis for planners and landscape architects in designing the development of communities, especially those at grassroot or informal communities. An expert consultation and sample community play testing are conducted to further refine the toolkit. A project case study at Artex Compound, a marginalized low-lying community in Malabon City that has been living with water since 2004 and is dubbed the “Venice of the Philippines”, also tests out the toolkit’s application in community planning. The case study allows the use of the toolkit through a focus group discussion and future landscape scenario workshop with the stakeholders of Artex Compound, helping the community visualize a community landscape development plan. Overall, the study provides a basis for how community planning toolkits can be developed from a feminist standpoint with integration of game theory, providing recommendations on how to further develop and strengthen community planning toolkits.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Game theory; Landscape Planning -- Malabon City (Philippines); Community development -- Malabon City (Philippines); Landscape architecture and women -- Malabon City (Philippines)